2013
DOI: 10.1111/dom.12022
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia is associated with impaired pulsatile insulin secretion: effect of basal insulin therapy

Abstract: Hyperglycaemia in type 2 diabetes is associated with a reduction in postprandial insulin secretion, specifically through a reduction in insulin pulsatility. Reducing chronic hyperglycaemia by basal insulin therapy enhances endogenous β-cell function in the postprandial state. These data support the use of basal insulin regimens in the pharmacotherapy of overtly hyperglycaemic patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
(63 reference statements)
0
12
1
1
Order By: Relevance
“…Later studies confirmed the impaired insulin pulsatility of T2DM patients (e.g. [14], [15], [16]; but see [17]).…”
Section: Introductionmentioning
confidence: 82%
“…Later studies confirmed the impaired insulin pulsatility of T2DM patients (e.g. [14], [15], [16]; but see [17]).…”
Section: Introductionmentioning
confidence: 82%
“…The present data illustrate that the exaggerated GLP-1 response in patients with type 2 diabetes seems to be the main explanation for the improvement in β-cell function after RYGB in response to a meal. Reduced glucotoxicity may play a role in the improved β-cell function after surgery, but it seems to be of minor importance compared with the actions of GLP-1 (40,41). Of note, HOMA-IR was not different between saline and Ex-9 infusion at any visit.…”
Section: Discussionmentioning
confidence: 99%
“…Basal insulin based BOT is recommended as the first step of insulin introduction overseas since it is considered as a safe insulin regimen with less hypoglycemia risk, as well as a simple treatment compared with multiple daily insulin injections because it involves only once daily insulin injection [3]. There is a study which suggested that it improved endogenous insulin secretory function by rectifying fasting glucose to near normal level [8].…”
Section: Discussionmentioning
confidence: 99%